INTERFERENSI BAHASA SUNDA KE DALAM BAHASA INDONESIA PADA ANAK SEKOLAH DASAR KELAS 4-6 - Santi Wulandari; Vini Apriliani; Wikanengsih Wikanengsih (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
The research is motivated by the use of two languages in communicating both oral and written so that the disturbance of  Sundanese language into Indonesian and Indonesian into the Sundanese language. The purpose of this research is to know as well as to record the forms of interference Sundanese language into Indonesian and Indonesian into the language of Sundanese in grade 4-6 student Ciptamarga 2 and grade 4-6 student Ciptamarga 3. This research uses descritive, from the results of research that has been done, researchers found leksikal interference in the language there are 75, while leksikal interference Sundanese the are 67. Of all the utterances delivered by the sample, the word is often used by students who use Indonesian language that is (bapa, sapedah, karangjang). The word that is often used by student who use Sundanese is (paman, laki-laki), so that happened very clear interference happened to the student.